2015
DOI: 10.11591/ijere.v4i2.4496
|View full text |Cite
|
Sign up to set email alerts
|

Investigating SATS-36 for a Matriculation Sample

Abstract: Students’ attitudes towards statistics have been more often negative due to many factors such as initial perception of the subject, low ability in mathematics and lack of motivation to study statistics. Studies involving SATS-36 included investigation of the different factors in relation to students’ attitude towards statistics. Other studies have investigated the structure of SATS-36 and the relationship between the different components of SATS-36. The research investigated the reliability and validity of SAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Most of the past studies only compared the gender and age. For instance, Krishnan & Idris (2015) and Coetzee & van der Merwe (2010) reported that male students displayed a more positive attitude toward statistics compared to female students. While for the age characteristic, older students perceived statistics to be less tough than younger students and also displayed slightly more positive attitudes towards statistics (Coetzee & van…”
Section: Introductionmentioning
confidence: 99%
“…Most of the past studies only compared the gender and age. For instance, Krishnan & Idris (2015) and Coetzee & van der Merwe (2010) reported that male students displayed a more positive attitude toward statistics compared to female students. While for the age characteristic, older students perceived statistics to be less tough than younger students and also displayed slightly more positive attitudes towards statistics (Coetzee & van…”
Section: Introductionmentioning
confidence: 99%